A qualitative study to explore strategies to improve the Road to Health Application for maternal and child health outcomes in South Africa - Dietrich, Janan Janine; Tsotetsi, Lerato; Dubazane, Thenjiwe; Tshabalala, Gugulethu; Maimela, Boitumelo; Weiss, Martin; Mulaudzi, Mamakiri (Frontiers in Digital Health, 2023)
Background The Road to Health Application (RTHA) is essentially a digitalized version of the National Department of Health’s Road to Health book, and a hand-printed booklet given to mothers at the birth of each baby. The RTHA, like the booklet, provides guidelines for maternal and child health outcomes, with the goal of creating a database of children and caregivers in South Africa and teaching them how to raise a healthy child. This paper explored potential barriers and enablers to using the RTHA in the South African context based on user experiences. Methods Using a qualitative design, we conducted 50 serial interviews (two separate interviews, 1 month apart). Through convenience, sampling eligible participants were 18 years or older women who were pregnant and/or had a child under the age of 5 years. Participants included 25 existing users and 25 new users of the RTHA, who owned android smart phones at enrollment. Existing users were recruited telephonically through the National Department of Health database, and new users were approached at the antenatal care unit and wellness baby clinic (women with children under 5 years) at the Chris Hani Baragwaneth Academic Hospital. Upon enrollment, participants completed a brief survey on sociodemographics and mobile phone use, and thereafter, they had a baseline interview followed by a telephonic interview 1 month later. A semistructured interview guide was used to explore barriers, enablers, and the usability of the RTHA. Using thematic data analysis, we identified enablers and barriers to the use of the RTHA. Results A third (33%) of all participants reported IsiZulu as their main language of communication, and 6% of the participants reported English as their main language of communication. The RTHA was an important addition to the booklet that helped keep new mothers informed about child immunization and provided important information about healthy child rearing practices. However, multiple barriers were cited to using the RTHA; these included the fact that the app was only available in two languages, high data costs, lack of access to smart phones, and app functionalities. The enablers to using the RTHA included the accessibility of important information regarding prenatal and postnatal childcare. Conclusion This study gives insight into the barriers and enablers from the end-user perspective to improve the RTHA for future use in South Africa and offers guidance on how to improve the RTHA to be more user-friendly, which could increase its usability among mothers. It further emphasizes the need to consider the challenges experienced by users in South Africa when developing future mobile health interventions to increase uptake.